EVALUATION OF ANTIOXIDATIVE ACTIVITY AND CHEMICAL COMPOSITION OF ETHANOLIC EXTRACT FROM AMANITA VAGINATA (BULL.) LAM.: AN IN VITRO STUDY - Paloi, Soumitra; Acharya, Krishnendu (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: The objective of this study was to evaluate free radical scavenging capacity and presence of bio-active components responsible for the activity in ethanolic fraction of Amanita vaginata (EfraAva). Methods: Antioxidant activity of ethanolic extract of A. vaginata was determined by using various processes and also investigated for bioactive components such as total phenol, total flavonoid, ascorbic acid, ß-carotene and lycopene. Results: The results showed that EfraAva has good antioxidant activity and EC50 values of the extract was in the order of chelating ability of ferrous ion< reducing power< DPPH radical scavenging. Conclusion: Thus it can be suggested that fraction of A. vaginata may be used as a natural additive in food and pharmaceutical industries. Key words: Antioxidant activity, Chelating ability of ferrous ions, DPPH, Edible mushroom, Free radicals, Phenolic compounds, Reducing power